Ibn al-Nafis - Anwar, Owais; Ansar, Farrukh (International Journal of Pathology, 2018)
There had been tremendous contributions ofGreat Muslim Scientists and Great Patrons ofSciences and Research in laying the foundationsof modern sciences; without which perhaps theworld would still be in the dark ages! Their greatvisionary, laborious and honest work paved theways for renaissance, industrialization andsuperb reforms in educational